Energy Resilient Design for All Income Economies: Exploring backup system and lighting needs when experiencing power outages - Sevelius, Nelly (My University, 2022)
Due to a transition towards sustainability and a growing dependency on electricity, disturbances and limitations in electricity supply are expected to increase. Already, an insecure electricity supply exists in low- and lower-middle-income economies. Therefore, the first aim of this master’s thesis was to investigate everyday life in low- and lower-middle-income economies regarding energy resilience. The second aim was to explore the possibility of a design proposal for all income economies within a narrowed down area, which came to be lighting and backup systems when experiencing power outages. Practice-oriented exploration and analysis were performed, investigating the first aim, mapping household practices in low- and lower-middle-income economies concerning energy resilience. The second aim was explored through a Research through Design approach, which commenced with an idea generation and elimination process, resulting in eight design proposals created through individual brainstorming and two co-creation sessions with participants from different income economies. Lastly, the design proposals were evaluated through a survey and interviews, where the answers were quantitatively and qualitatively thoroughly analyzed. From this study, many of the practices performed in low- and lower-middle-income economies were already energy resilient. However, practices such as communicating, entertaining, and educating were generally not as energy resilient; how lacking depends on the household’s habits, general meanings, and competences. The result of the study indicates that a design proposal for all income economies is possible, while there is a plurality of individual factors affecting when designing within the area. Also, unity in the households from all investigated income economies was found, where all seem to prefer easily accessible and implemented solutions that function with a small effort. This result is affirmed through two concepts being preferred in all income economies. Thus, this master’s thesis contributes to one way of preparing for the dilemma of future disturbances and limitations in households’ electricity supply.
Keywords: energy resilience, income economies, power outages, backup system, lighting, future design, sustainability, design for all, research through design